Early postnatal right-to-left patent ductus arteriosus shunting and severe outcomes in neonates with congenital diaphragmatic hernia: a retrospective cohort study - Jung Il Kwak; Juhee Park; Mi Jin Kim; Kyusang Yoo; Bo Kyeong Jin; Tae-Gyeong Kim; Joo Hyung Roh; Ha Na Lee; Keon Hee Seol; Chae Young Kim; Soo Hyun Kim; Jiyoon Jeong; et al. (BMC Pediatrics)
Abstract Background Congenital diaphragmatic hernia (CDH) is a severe anomaly associated with significant pulmonary hypertension (PH) and high mortality, often requiring extracorporeal membrane oxygenation (ECMO). Early prognostic markers are essential to guide clinical decisions. This study evaluated the prognostic value of right-to-left (R-L) shunting in the patent ductus arteriosus (PDA) during the early postnatal period in predicting ECMO use and mortality in neonates with CDH. Methods This retrospective cohort study included neonates with CDH admitted between 2013 and 2024. Echocardiographic evaluations within 24 h of birth categorized PDA shunting as left-to-right (L-R), R-L, or bidirectional. Outcomes were analyzed using two models. First, the pure R-L shunt group was compared with the combined L-R and bidirectional shunt groups. Second, bidirectional shunts were subclassified as L-R or R-L predominant based on Doppler spectral area, with the R-L predominant group analyzed together with the pure R-L shunt group and the L-R predominant group analyzed with the L-R shunt group. Primary outcomes were ECMO use or mortality, analyzed using logistic regression. Results Among 145 neonates, both models demonstrated that R-L shunting was associated with a higher ECMO requirement or increased mortality rate compared to L-R shunting (p < 0.001). Multivariate analysis identified R-L shunting as an independent predictor of adverse outcomes (Model 1: odds ratio [OR] 6.785, 95% confidence interval [CI] 2.333–19.730; p < 0.001; Model 2: OR 4.067, 95% CI 1.444–11.455; p = 0.008). Conclusion The direction of early postnatal R-L PDA shunt, assessed within 24 h of birth, was significantly associated with ECMO use or mortality in neonates with CDH.